2003
DOI: 10.1379/1466-1268(2003)008<0303:calbtc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

CHIP: a link between the chaperone and proteasome systems

Abstract: CHIP, carboxy terminus of Hsc70 interacting protein, is a cytoplasmic protein whose amino acid sequence is highly conserved across species. It is most highly expressed in cardiac and skeletal muscle and brain. The primary amino acid sequence is characterized by 3 domains, a tetratricopeptide repeat (TPR) domain at its amino terminus, a U-box domain at its carboxy terminus, and an intervening charged domain. CHIP interacts with the molecular chaperones Hsc70-Hsp70 and Hsp90 through its TPR domain, whereas its U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
345
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(365 citation statements)
references
References 24 publications
(39 reference statements)
6
345
0
5
Order By: Relevance
“…Recently, CHIP has been implicated in progression of the pathophysiological conditions of various neurodegenerative diseases. 8,9,11,12,28,46,47 However, the molecular mechanisms regulating the functions of CHIP in these pathophysiologic conditions are not clearly elucidated. In the present study, we identify that CHIP and Cdk5 act as critical factors to regulate the level of the toxic protein, tAIF, during oxidative stress-induced neuronal death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, CHIP has been implicated in progression of the pathophysiological conditions of various neurodegenerative diseases. 8,9,11,12,28,46,47 However, the molecular mechanisms regulating the functions of CHIP in these pathophysiologic conditions are not clearly elucidated. In the present study, we identify that CHIP and Cdk5 act as critical factors to regulate the level of the toxic protein, tAIF, during oxidative stress-induced neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…CHIP is composed of three major domains: (1) an aminoterminal three tetratricopeptide repeat (TPR) domain interacting with Hsc/Hsp70 and Hsp90, (2) a highly charged central domain with unknown functions and (3) a carboxyl-terminal U-box domain conferring E3 ubiquitin ligase activity. [8][9][10] Based on these domains, it has been indicated that CHIP has a crucial role as a molecular co-chaperone in the maintenance of protein homeostasis during cellular stress and recovery. 8,[11][12][13] Indeed, CHIP has been demonstrated to serve as a crucial catalyst for ubiquitination of Hsp70 client proteins targeting for proteasome-dependent degradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CHIP functions as a co-chaperone of Hsp70, interacting with the chaperones through its TPR (tetratricopeptide repeat) domain, and also possesses an E3 ligase activity which is mediated by the U-box domain (McDonough and Patterson 2003). Thus CHIP can provide a link between the chaperones and UPS and probably regulates the balance between protein refolding and degradation in the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Findings that CHIP interacts with the S5a subunit of proteasomes and co-localizes with the proteasomes in cells have led to a suggestion that CHIP also participates in substrate delivery to the proteasomes (McDonough and Patterson 2003). Bag-1, another cochaperone of Hsp70, has also been implicated in the sorting of substrates to proteasomes (Demand et al 2001;Alberti et al 2002).…”
Section: Introductionmentioning
confidence: 99%